Robot Self-Balancing Berbasis LEGO Mindstorm EV3 Untuk Pembelajaran Robotika - Kenny, Adrian; Christiand, Christiand; Kurniawan, Riccy; Christiand (Cylinder : Jurnal Ilmiah Teknik Mesin, 2025)
Robotics education must be implemented effectively to develop students' conceptual understanding and technical competencies. One relevant approach involves the development of self-balancing robots as an exemplary platform that facilitates learning in mechanical design, control systems, and sensor programming. The success of this approach critically depends on the appropriate selection of both tools and methodologies. The LEGO Mindstorms EV3 platform is an ideal tool due to its assembly convenience, design flexibility, and seamless hardware-software integration for robotic development. Implementing a LEGO Mindstorms EV3-based self-balancing robot provides valuable learning opportunities in robotic control algorithms utilizing gyroscopic sensors, ultrasonic sensors, and servo motors. This research work presents the design and implementation process of a LEGO Mindstorms EV3-based self-balancing robot as an innovative educational tool for robotics. The platform supports integrated mastery of theoretical concepts and technical skills, fostering comprehensive engineering and control systems learning.